A Persuasive Study on Burnout and Psychological Disorders among Medical Practitioners and Health Care Staff During Pandemic and Overload Work Environment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Burnout syndrome in recent days has creeped among the medical practitioners and supportive staffs in hospitals and health care units from around the globe, due to the pandemic situation that provoked because of COVID-19. Incessant flow of patients round the clock shattered the energy level of physicians and nurses who are in this life saving exercise without even caring about their own lives. But treating patients continuously in critical care unit leads to emotional fatigue and in a long run leads to futility among the health care workers. Analysing the root cause among the medical practitioners by means of their lifestyle, socio-psychological status and their inbuilt aptitudes will let the hidden reasons behind this burnout. By means of continuous monitoring, motivation and training they can overcome this syndrome and make their lives more meaningful for this society as well as their self. This paper reveals the common and psychological problems obsessed by the physicians during at their work place, their personal and social life situations with reference to studies carried out in different parts of the world.